(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
Nina Paley (NP) is an American cartoonist, animator, and free culture activist from Central Illinois, United States. She was the artist and often the writer of the comic strips Nina’s Adventures and Fluff, after which she has worked primarily in animation. She is best known for creating the 2008 animated feature film Sita Sings the Blues, based on the Ramayana, with parallels to her personal life. In 2018, she completed her second animated feature, Seder-Masochism, a retelling of the Book of Exodus as patriarchy emerging from goddess worship. Barbara Pollak-Lewis (BPL) is a painter, curator and art educator from San Francisco, CA. She studied Animation at the Rhode Island School of Design. She has followed Nina’s cartoons since the late 1980s.